(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Various kind of human development is resulting in different kind of pollution to the water resources . Monitoring of Drinking water quality and its serious analysis is very significant relative to access the human health hazards. This paper is an attempt for the same purpose. The samplewere collected from main areas of the Bikaner City and were analysed for the desired physiochemicalparameters applying the internationally valid standard methods